IKN HAS THE POTENTIAL TO DAMAGE THE ENVIRONMENT: AN ANALYSIS OF THE LEGAL POWER OF IKN BASED ON THE ENVIRONMENTAL LAW - Tamaulina Br Sembiring; Budi Sulistiyo Nugroho; Didik Suhariyanto; Mardi Widodo; Emmi Rahmiwita Nasution (Faculty of Law, Universitas Pekalongan, 2023)
One of the primary difficulties in the development of the Indonesian National Capital (IKN) is the environment. According to predictions, the construction of IKN infrastructure could have an adverse effect on the environment, potentially affecting biodiversity, regional landscape quality, the amount of carbon stored in the forests, water availability, pollution, trash, noise, and drainage systems. In addition to having an influence on the environment, IKN development may also have an impact on social issues including land disputes brought on by property seeking and unauthorized land use. A conceptual and statutory approach is applied in the study method used to investigate current legal issues. The purpose of this research is to examine and assess how the government should manage and safeguard the environment in light of the move of the country's capital. The findings of this study suggest that shifting the country's capital will have an impact on the region around Kutai Kartanegara Regency. The management and conservation of the environment in the territory designated as the new nation's capital falls under the purview of the government, particularly regional governments. If someone violates or does not abide by the sustainability and welfare of the region, legal action can be taken, including administrative measures like filing objections, preventive and repressive protection, as well as providing sanctions in the form of fines and imprisonment.